Experimental study on the correlation between the partial and total salt content in saline gravel using ion chromatography. (January 2021) - Wang, Liyang; Liu, Jiankun; Yu, Xinbao; Li, Xu; Puppala, Anand J.; Wang, Qi
Highlights: The partial and total salt contents in saline gravel are significantly correlated. The errors due to simplification of the theoretical model range within Â±10% . Proposed new method generating calibration curves using ion chromatography. Abstract: Soluble salt content is one of the most basic and important characteristics of saline soils. It dominates the physical properties of saline soils and governs the selection of remedial measures on the sites. Failing to determine the total salt content of coarse-grained soils may bring potential salt-induced problems in railway and highway infrastructures. However, the existing measurement methods of salt content fail to determine the total salt content of gravel, consequently hindering the theoretical analysis of the mechanisms associated with salt content in the gravel. To address the need for determining the total salt content of gravel, a relationship between the partial and total salt content of gravel has been developed through a theoretical model, which has then been simplified to make it more readily applicable. Gravel samples with different types of soluble salts (sodium sulfate, sodium chloride, magnesium sulfate, and potassium chloride), fine pure soil content (15%, 25%, 35%, and 45%), and sieving attributes (sieve size = 1, 2, and 5 mm), were tested for partial salt content using ion chromatography. The test results show that the partial and total salt contents are significantly correlated, and that a sieve with a pore size of 5 mm exhibits the most conducive results. The occurrences of sodium sulfate and sodium chloride have limited influence on the distribution and measurement of each other as the total salt content is relatively small. The calculated ratio z of the salt passing rate to that of fine pure soil lies within a relatively narrow band with varying salt types, fine pure soil content, and sieve sizes. For a known partial salt content, the total salt content of the gravel can be approximately estimated by the theoretical model through empirical values of z, or more accurately predicted by the proposed new calibration method.